Skateboarding and urban landscapes in Asia : endless spots - McDuie-Ra, Duncan (Consumption and sustainability in Asia., 2021)
As urban development in Asia has accelerated, cities in the region have become central to skateboarding culture, livelihoods, and consumption. Asia's urban landscapes are desired for their endless supply of 'spots'. A spot is assemblage of objects, surfaces and obstacles holding the possibilities to perform skateboarding manoeuvres (tricks). Spots are not built for skateboarding; they are accidents of urban planning and commercial activity; glitches in the urban machine. Skateboarders and filmers chase these glitches searching for spots to make skate video, the currency of the industry and skateboarding's primary cultural artefact. Once captured, performances at Asia's spots circulate rapidly through digital platforms to millions of skateboarders, enrolling spots from Shenzhen, Dubai and Ramallah into an alternative cartography of the region. By focusing on this alternative way of desiring and consuming urban Asia, this book explores the ways skateboarding resets relational and comparative hierarchies of urban development within Asia and between Asia and the West.